Exact solution of an Ising model with competing interactions on a Cayley tree - Ganikhodjaev, Nasir; Pah, Chin Hee; Wahiddin, Mohamed Ridza (IOP Publishing, 2003)
The exact solution of an Ising model with competing restricted interactions on the Cayley tree, and in the absence of an external field is presented. A critical curve is defined where it is possible to get phase transitions above it, and a single Gibbs state is obtained elsewhere.